1245Culturally-appropriate research supporting a co-designed childhood obesity prevention program tailored for Māori & Pacific Islanders. (2nd September 2021) - Hardt, Jessica; Matautia, Brent; Tanuvasa, Elkan; Peu, Tevita; Kira, Kirstine; Santos, Daphne; Brignano, Sebastien
Abstract: Background: Children of Māori & Pacific Islander descent living in Australia experience higher rates of obesity, increasing their risk of developing life diminishing chronic diseases. However, community-based, childhood obesity prevention programs, tailored to the Māori & Pacific Islander population are lacking, further escalating the rates of health inequity. Methods: Program co-design involved a three-phase, iterative, participatory and experienced-based process, guided by the Te Ara Tika: Guidelines for Māori Research Ethics, promoting respect and equity. Following traditional oratory customs of Māori & Pacific Islander cultures, "talanoa" facilitated the collaborative program design with consumers, cultural advisors and health professionals. Results: Co-design developed an 8-week community-based childhood overweight/obesity prevention program, providing culturally-tailored education across nutrition, physical activity and parenting practices. Maximum engagement demonstrated life-changing improvements across the life course; 72% of children and 67% of parents reduced their sugar sweetened beverage consumption and 60% of children and 47% of adults increased their vegetable consumption. Resultingly, BMI z-score decreased among 59% of children and BMI decreased among 47% of parents. Conclusions: Endorsing a bottom-up approach, via a co-design methodology, significantly improves culturally-tailored health care delivery. An evidence-based framework developed holds significant potential to be scaled to additional cultural groups. A consumer-led approach is pivotal to sustaining engagement and improving health outcomes, addressing health inequity among Australia's priority populations. Key messages: Co-design empowered consumers to formulate program objectives, session plans, resources and evaluation tools. Co-designed quality improvement practices ensure relevance of the program to sustainably address community needs, tackling the complexities of obesity over generations.